Multisensory Interactive Media as Menstrual Fiqh Education for Children of Concrete Operational Age - Yusrina, Jihan Avie; Nugraini, Erna Dwi; Azizah, Nurul; Aklis, Mohammad Zainudin (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to investigate the actual conditions of menstrual fiqh education for children at the concrete operational stage and to develop an interactive multisensory product based on Islamic values ​​as a learning medium that is appropriate to the characteristics of children's cognitive development. This study uses a Research and Development (R&D) methodology by adapting the three initial stages of the 4D model developed by Thiagarajan and Semmel, namely the Definition, Design, and Development stages. The results of the study indicate that the developed product is able to meet the targeted learning outcomes and obtain a very high level of validity, with a score of 96.42% from fiqh experts, 91.07% from media experts, and 88.89% from limited users. These findings indicate that interactive multisensory media based on Islamic values ​​has significant potential as an effective, contextual, and developmentally friendly educational tool in helping children understand the concept of menstrual fiqh appropriately, positively, and directed from an early age. The implications of the study emphasize the importance of integrating a multisensory approach and Islamic values ​​in children's reproductive health education to build a correct religious understanding, psychological readiness, and a positive attitude towards biological changes.